The Research of the Establishing a Design Process Framework for Museum Exhibition Design - Lin, Chung-Hung (IJRDO-Journal of Applied Science, 2015)
Museum exhibition styles have changed remarkably over the past few decades because they have generally followed the evolution of social and cultural circumstances and the adoption of new technology. Today, exhibition design is important element for establishing a more professional status for museums and other institutions (Velarde, 1990). The study provides theoretical application by proposing a particular form of inter-disciplinary museum exhibition design framework. The outcome of this study, therefore, is to create a conceptual design concerning the following approaches will be: (1) A conceptual framework for the design planning that allows designers to cope with the complexity of co-ordination between all participants involved museum exhibition design. (2) A multi-disciplinary systematic framework which can be described as a plan of design activity, particularly for museum exhibition design to achieve design aim. Keywords: museum exhibition, design process framework, inter-disciplinary, curator, multi-disciplinary